Improving the implementation of tailored expectant management in subfertile couples: protocol for a cluster randomized trial - van den Boogaard, Noortje M (BioMed Central, 2013)
BACKGROUND: Prognostic models in reproductive medicine can help to identify subfertile couples who would benefit from fertility treatment. Expectant management in couples with a good chance of natural conception, i.e., tailored expectant management (TEM), prevents unnecessary treatment and is therefore recommended in international fertility guidelines. However, current implementation is not optimal, leaving room for improvement. Based on barriers and facilitators for TEM that were recently identified among professionals and subfertile couples, we have developed a multifaceted implementation strategy. The goal of this study is to assess the effects of this implementation strategy on the guideline adherence on TEM. METHODS/DESIGN: In a cluster randomized trial, 25 clinics and their allied practitioners units will be randomized between the multifaceted implementation strategy and care as usual. Randomization will be stratified for in vitro fertilization (IVF) facilities (full licensed, intermediate/no IVF facilities). The effect of the implementation strategy, i.e., the percentage guideline adherence on TEM, will be evaluated by pre- and post-randomization data collection. Furthermore, there will be a process and cost evaluation of the strategy. The implementation strategy will focus on subfertile couples and their care providers i.e., general practitioners (GPs), fertility doctors, and gynecologists. The implementation strategy addresses three levels: patient level: education materials in the form of a patient information leaflet and a website; professional level: audit and feedback, educational outreach visit, communication training, and access to a digital version of the prognostic model of Hunault on a website; organizational level: providing a protocol based on the guideline. The primary outcome will be the percentage guideline adherence on TEM. Additional outcome measures will be treatment-, patient-, and process-related outcome measures. DISCUSSION: This study will provide evidence about the effectiveness and costs of a multifaceted implementation strategy to improve guideline adherence on TEM. TRIAL REGISTRATION: http://www.trialregister.nlNTR3405. This study is sponsored by ZonMW.